DNA framework carriers with asymmetric hydrophobic drug patterns for enhanced cellular cytotoxicity. Issue 3 (12th December 2022) - Zhao, Yan; Guo, Linjie; Cao, Shuting; Xie, Mo; Peng, Hongzhen; Li, Jiang; Luo, Shihua; Ma, Lan; Wang, Lihua
Abstract : The asymmetric hydrophobic drug patterns created on DNA frameworks induced enhanced cellular cytotoxicity. Abstract : We devise a class of amphiphilic drug complexes by programming hydrophobic drug patterns (HDPs) on DNA frameworks. We investigate the effect of HDPs on cellular uptake efficiency and drug potency. We achieve enhanced cytotoxicity against tumor cells by using an asymmetric HDP.